Relação entre os fatores contingenciais e a remuneração variável de executivos - Martins, Vanessa de Quadros (Universidade do Vale do Rio dos Sinos, 2019)
The research deals with executive compensation, an essential element of management accounting. The objective was to analyse the relationship between the contingency factors (environment, strategy, structure, technology) and executive compensation. The research is quantitative and primary and secondary data of publicly traded companies that operate in Brazil were used to investigate the hypotheses. The technique used was the generalized structural equations model (GSEM). It is necessary to study the Brazilian context, since the country has peculiar characteristics about the remuneration of other countries, as the lower taxation and payments are, in the majority, in the form of a financial resource to the detriment of the payment in the form of stock options. The hypotheses were accepted for the most part and showed that companies that employ the defensive strategy pay lower variable compensation in the form of shares since the result is less dependent on the executive's performance. It has also been found that the more centralized the companies are the lower the use of technology, the higher the tendency to pay in variable form. In addition, it was also found that the more robust and better-performing companies pay higher variable compensation in the form of shares. Only the environment variable showed no relation to the variable remuneration. The sector control variable was not significant, which is evidence that the sector does not influence the association between the contingency factors and the variable compensation. This fact confirms the thesis that three contingency factors are related to the variable remuneration of executives in the form of shares. The study directs advances in the Contingency Theory, showing that there is a relation between three contingency factors analysed (strategy, structure, technology) and executives’ compensation in the form of shares. Regarding management accounting, it shows the importance for companies to consider the factors contingent to their activities, since these are associated to the lower or greater payment of variable executives’ compensation, which can stimulate the congruence of objectives, enhancing performance. The research differs from the existing literature by considering the influence of contingency factors on executives’ compensation.
Keywords: Fatores contingenciais; Remuneração de executivos; Contabilidade de gestão; Contingency factors; Executives’ compensation; Management accounting; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis